PEMANFAATAN LIMBAH SERAT DAUN NANAS (ANANAS COMOSUS) SEBAGAI TALI SERAT ALAMI (The Utilization of Pineapple Leaf’s Waste as a Natural Fiber Ropes) - Eryanto Hutabarat; Riswanti Sigalingging (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT   Pineapple plant is one of the most popular plant in the world. Pineapple plants will produce fruits  after 1-2 years of planting and die than after fruiting them  producing 70 leaves. The purpose of this research was to find the value of the effect of variety (Cayenne and Queen) and the location of pineapple leaves (top, middle and bottom) on maximum load, elasticity, and water absorption. The maximum load of the upper, middle, and lower  of Queen varieties leaf  were 157.84 kg, 166.83 kg, 157. 84 kg while the value of Cayenne varieties leaf were 191.77 kg, 195.66 kg, 120. 08 kg respectively. The elasticity of the upper, middle, lower turtle Queen varieties were 69.13 MPa, 69.38 MPa, 76.12 MPa and the value of the Cayenne varieties leaf were 90.83 MPa, 88.69 MPa, 48.07 MPa respectively. The value  of 1 hour water immersion’s absorption  of Queen varieties on upper, middle and lower leaves were 84.33%, 74.33%, 76%, while the Cayenne varieties of leaves were 91.67%, 91%, 91 % respectively. The water absorption in the upper, middle, and lower of Queen varieties leaf in 6-hour immersion was 111.33%, 95.67%, 94%, while for the Cayenne varieties leaf  were 112%, 100.67%, 105.67 % respectively. The value of maximum load and water absorption on pineapple leaf fiber rope did not reach SNI standard and was recommended to be used as a textile’s material. Keywords: waste, pineaple, fiber, tensile test. ABSTRAK Tanaman nanas merupakan tanaman yang sangat digemari dunia. Tanaman nanas  berproduksi setelah 1-2 tahun ditanam dan mati setelah berbuah serta menghasilkan 70 helai daun. Tujuan dari peneliian ini untuk mengetahui pengaruh varietas (Cayenne dan Queen) dan letak daun nanas (atas, tengah dan bawah) terhadap beban maksimal, elastisitas dan daya serap air. Beban maksimal dari varietas Queen daun atas, tengah dan bawah adalah 157,84 kg, 166,83 kg, 157, 84 kg sedangkan untuk varietas Cayenne daun atas, tengah dan bawah  adalah 191,77 kg, 195,66 kg, 120,08 kg. Elastisitas dari varietas Queen daun atas, tengah, dan bawah adalah 69,13 MPa, 69,38 MPa, 76,12 MPa dan nilai dari varietas Cayenne daun atas, tengah dan bawah adalah 90,83 MPa, 88,69 MPa, 48,07 MPa. Daya serap air   perendaman 1 jam varietas Queen daun atas, tengah, dan bawah adalah 84,33%, 74,33%, 76 %, sedangkan varietas Cayenne daun atas, tengah, dan bawah adalah 91,67%, 91%, 91%. Daya serap air varietas Queen daun atas, tengah dan bawah pada perendaman 6 jam adalah 111,33%, 95,67%, 94%, sedangkan untuk varietas Cayenne daun atas, tengah dan bawah adalah 112 %, 100,67%, 105,67%. Nilai beban maksimal dan daya serap air tali serat daun nanas tidak mencapai standar SNI dan disarankan untuk pembuatan tekstil.   Kata Kunci: limbah, nanas, serat, uji tarik.